Implementasi Video Dongeng Berbasis Kearifan Lokal pada Kemampuan Literasi Siswa Kelas IV Sekolah Dasar - Aditya Rini Kusumaningpuri (Jurnal Didaktika Pendidikan Dasar, 2023)
Video fairy tales based on local wisdom are used to facilitate literacy because they can concretize teaching material that is abstract in nature. The purpose of this study was to describe the effectiveness of fairy tales based on local wisdom on the literacy skills of fourth grade elementary school students. The research was conducted in class IVA SDIT MTA Matesih with a total of 28 students. The research method used is qualitative research. The type of research used is a qualitative descriptive approach. Data collection techniques using interviews, documentation and observation. The results of the study show that (1) The use of local wisdom-based fairy tale learning videos for fourth grade elementary school students can create a conducive learning process; (2) In the process of teaching fairy tales based on local wisdom, the teacher uses 4 stages, namely giving apperception, showing fairy tales with a live playback process and with a pause system for each point, direct discussion or question and answer, and evaluation through questions or presentations; (3) Students' literacy ability to mention intrinsic elements and retelling ability increased from an average of 88 to 86. It can be concluded that the use of effective local wisdom-based fairy tale videos is used to improve students' literacy skills.